Robotic nipple-sparing mastectomy for cancer risk reduction: demonstration of applicability and surgical results - Rodrigo Bernardi; José Clemente Linhares; Audrey Tsunoda; Sérgio Bruno Bonatto Hatschbach; Reitan Ribeiro; Anne Karoline Groth; Isabeli Lopes Kruk (Brazilian Journal of Oncology)
Introduction: Robotic nipple sparing mastectomy (RNSM) may be a breakthrough for breast cancer risk reduction surgeries, providing better aesthetic results. This study aims to spread the knowledge of the robotic surgical technique, still little performed in the world, and to demonstrate the applicability and surgical results.